The global regulatory logic of organ regeneration: circuitry lessons from skin and its appendages. (17th June 2021) - Yue, ZhiCao; Lei, Mingxing; Paus, Ralf; Chuong, Cheng‐Ming
ABSTRACT: In organ regeneration, the regulatory logic at a systems level remains largely unclear. For example, what defines the quantitative threshold to initiate regeneration, and when does the regeneration process come to an end? What leads to the qualitatively different responses of regeneration, which restore the original structure, or to repair which only heals a wound? Here we discuss three examples in skin regeneration: epidermal recovery after radiation damage, hair follicle fate choice after chemotherapy damage, and wound‐induced feather regeneration. We propose that the molecular regulatory circuitry is of paramount significance in organ regeneration. It is conceivable that defects in these controlling pathways may lead to failed regeneration and/or organ renewal, and understanding the underlying logic could help to identify novel therapeutic strategies.